Examining the predictive accuracy of the novel 3D N‑linear algebraic molecular codifications on benchmark datasets - García‑Jacas, César R.; Contreras‑Torres, Ernesto; Barigye, Stephen J.; Cabrera‑Leyva, Lisset (Journal of Cheminformatics, 2016)
Recently, novel 3D alignment-free molecular descriptors (also known as QuBiLS-MIDAS) based on two-linear, three-linear and four-linear algebraic forms have been introduced. These descriptors codify chemical information for relations between two, three and four atoms by using several (dis-)similarity metrics and multi-metrics. Several studies aimed at assessing the quality of these novel descriptors have been performed. However, a deeper analysis of their performance is necessary. Therefore, in the present manuscript an assessment and statistical validation of the performance of these novel descriptors in QSAR studies is performed.
Keywords: Multiple Linear Regression; QuBiLS-MIDAS; 3D-QSAR; TOMOCOMD-CARDD